Discrete-time control system applicable to aerobic wastewater treatment process (Research, Society and Development, 2021)
In this work, the Optimal Control Theory was used to develop a discrete-time controller, applicable to the aeration tanks of the activated sludge processes, a process widely used for the treatment of liquid effluents sanitary or industrial. The dynamic behavior of the state variables used to describe the aeration tank was described using the model proposed by the International Water Association. Biomass concentration, substrate concentration and effluent flow from the aeration tank constituted the state variables. Recirculation flow and sludge disposal flow acted as control variables. The computational simulations conducted indicated that the proposed controller allows to substantially reduce the oscillation times and variations in concentrations of state variables in relation to their equilibrium conditions.